ANALYSIS OF ASSESSMENT IMPLEMENTATION IN THE DEVELOPMENT OF RAUDHATUL ATHFAL'S CHILDREN IN SAGULUNG BATAM - Nurkamisah; Imamah; Eliza; Maelawati Suhardja; Rina Silfya (International Conferences on Early Childhood Education Proceedings, 2023)
This research aims to determine how to implement of assessment in observing the development of Raudhatul Athfal in Sagulung district using qualitative descriptive methods. Data collection was used by questionnaire method from 28 respondents consisting of 88.5% of University graduates and 50% of them have more than 5 years of teaching experience. Triangulation technique use data analysis through several processes, namely data reduction, data presentation and making conclusion. This study aims to analyze the assessment process and the types of instruments teachers used in classroom. Researchers identify barriers faced by teachers and provide solutions so that these problems can prevent or suppressed so that they do not become things that cause the learning process to be constrained or disrupted. The result showed that teachers were dominants, around 53.8% did a checklist. In addition, there were 50% of respondents who answered that in conducting their assessment they only observed during the learning process, did not take notes, document or record. Forgetting and erroneous elements can occur when giving assessments or explanations in the assessment instruments used because the teacher only gives assessments from memory. This makes the validity of the teacher's assessment results inaccurate and doubtful. Other research results found that there were differences in family background, the number of children in one class, children often did not come to school and teachers did not make use of digital facilities and this was an obstacle in the implementation of the assessment.